Education of The Importance of Hands Washing to Students at SDN Wanakerta 1 as a COVID-19 Prevention Effort - Irman Nurichsan; Ai Nur Asri; Muslim Muslim; Roro Wajdilfarah; Seli Seftiani5 (Fakultas Kewirausahaan Universitas Garut, 2022)
ABSTRACT The novel coronavirus or COVID-19 is reported to have claimed millions of lives worldwide, so far there has been no drug and vaccine that can cure patients infected with the virus from this type of corona. Meanwhile the number of positive patients is increasing because this virus is easily transmitted through droplets that come from coughing or sneezing which are then spread in the air or stick to surfaces of objects. The main step to prevent transmission is to wash hands after touching surfaces of objects in public so that education about the importance of washing hands is currently very important, especially for children who are included in the vulnerable group to be infected with the virus. ABSTRAK Novel coronavirus atau COVID-19 dilaporkan telah menelan jutaan korban jiwa di seluruh dunia, hingga saat ini belum ditemukan obat dan vaksin yang dapat menyembuhkan pasien yang terinfeksi virus dari jenis corona tersebut. Sementara itu angka pasien positif kian meningkat karena virus ini bersifat mudah menular melalui droplets yang berasal dari batuk atau bersin yang kemudian tersebar di udara atau menempel di permukaan benda. Langkah utama untuk mencegah penularan adalah dengan mencuci tangan setelah menyentuh permukaan benda di muka umum sehingga edukasi mengenai pentingnya mencuci tangan saat ini sangatlah penting terutama pada anak-anak yang termasuk kedalam kelompok rentan terinfeksi virus.